Analisis Pengaruh Openness to Experience dan Dukungan Sosial terhadap Kinerja Pegawai dimediasi Kepuasan Kerja di Kepolisian Daerah Sulawesi Barat - Wibowo, Muhammad Nuri; Dahri, Muh. Ilhamuddin; Muchtar, Muchtar; Nursiah, Nursiah; Syahrinullah, Syahrinullah (Journal of Management Branding, 2025)
This study was conducted with the aim of analyzing the influence of openness to experience, social support, and job satisfaction on employee performance, as well as to analyze the role of job satisfaction as a mediating variable in the relationship between openness to experience and social support on employee performance in the West Sulawesi Regional Police. This study used a quantitative method, with sampling using a purposive sampling technique with a total of 99 respondents. Data collection was carried out through a closed questionnaire, using a Likert scale of 1–5, limited interviews to validate contextual information, and document analysis to support descriptive data. Testing the quality of the research instrument used a validity test and a reliability test. The analytical tools used were classical assumption test analysis consisting of normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test; multiple linear regression analysis; path analysis; Sobel test analysis; then hypothesis testing used a partial test (t-statistic test), simultaneous test (F-statistic test), and coefficient of determination test. The results of the study indicate that: (1) openness to experience has a positive and significant effect on employee performance; (2) social support does not have a significant effect on employee performance; (3) job satisfaction is not able to mediate the relationship between openness to experience and employee performance; (4) job satisfaction is not able to mediate the relationship between social support and employee performance at the West Sulawesi Regional Police; (5) job satisfaction has an influence and is not significant on employee performance at the West Sulawesi Regional Police